2013
DOI: 10.1002/adhm.201300177
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‒Regulated Cardiomyogenic Differentiation Process of Mesenchymal Stem Cells by Enhancing the Expression of Extracellular Matrix Proteins and Cell Signaling Molecules

Abstract: The potential of graphene as a mesenchymal stem cell (MSC) culture substrate to promote cardiomyogenic differentiation is demonstrated. Graphene exhibits no sign of cytotoxicity for stem cell culture. MSCs are committed toward cardiomyogenic lineage by simply culturing them on graphene. This may be attributed, at least partially, to the regulation of expression levels of extracellular matrix and signaling molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(81 citation statements)
references
References 33 publications
4
70
0
1
Order By: Relevance
“…Park et al fi rstly proposed that graphene could upregulate the expressions of cardiomyogenic genes of MSCs and found that graphene promoted MSCs differentiate into the cardiomyogenic lineage without any exogenous chemical inducers. [ 156 ] The enhanced cardiomyogenic differentiation of MSCs cultured on graphene might be due to the upregulation of cell signaling molecules and gene expressions of ECM proteins. This fi nding indicated that graphene-based materials might be a novel platform for the cardiomyogenic differentiation of MSCs.…”
Section: Cardiac Regenerationmentioning
confidence: 99%
“…Park et al fi rstly proposed that graphene could upregulate the expressions of cardiomyogenic genes of MSCs and found that graphene promoted MSCs differentiate into the cardiomyogenic lineage without any exogenous chemical inducers. [ 156 ] The enhanced cardiomyogenic differentiation of MSCs cultured on graphene might be due to the upregulation of cell signaling molecules and gene expressions of ECM proteins. This fi nding indicated that graphene-based materials might be a novel platform for the cardiomyogenic differentiation of MSCs.…”
Section: Cardiac Regenerationmentioning
confidence: 99%
“…More recently, carbon nanomaterials such as CNT and graphene have been demonstrated to favor the attachment and cardiomyogenic differentiation of mesenchymal stem cells. [30][31][32] In addition, Notes: (A-C) Western blot showed activated β1-integrin protein expression in Bascs cultured on cNT-col scaffolds was twofold higher than those cultured on col scaffolds at day 7, while all β1-integrin remained roughly constant in these two groups. (D and E) Western blotting revealed the anti-β1-integrin antibody blocked the increase of α-actinin in the cNT-col group, while no apparent changes of α-actinin showed in Bascs grown in the control group.…”
Section: Discussionmentioning
confidence: 97%
“…Graphene-based materials are used in the field of bone repair or organ regeneration. Both GO and rGO are utilized in osteogenic stem cells to study [28][29][30] chondrogenesis [31], adipogenesis [32], epithelial genesis [32], myogenesis, cardiomyogenesis [33,34] and neurogenesis [35].…”
Section: Introductionmentioning
confidence: 99%